The Exposure Behavior and Perception of Marketing Communication Affecting Thai Tourists' Decision on Traveling by Train: A Case Study of Hua Lamphong Station - Sirimongkol, P.; Chandavimol, N. (Al-HIKMAH Journal, 2024)
The purpose of this study was 1) to study the exposure behavior of marketing communication affecting Thai tourists' decision on travelling by train at Hua Lamphong Station and 2) to study the perception of marketing communication affecting Thai tourists' decision on Traveling by Train at Hua Lamphong Station. The sample used in this study was 401 respondents who had previously travelled by train at Hua Lamphong Station between January 2022 and June 2023. The data was collected by using questionnaires. The statistics used to analyze the data were descriptive statistics including frequencies, percentage, mean, and standard deviation. The hypotheses were tested by using multiple regression analysis by enter regression method. The result showed that the exposure behavior of marketing communication in terms of the access and duration of exposure to marketing communication affected tourists' decision on traveling by train at a statistical significance level of 0.05. It also showed that the perception of marketing communication in terms of sales promotions, social network, and direct communication affected tourists' decision on traveling by train at a statistical significance level of 0.05.